2015
DOI: 10.21307/apex-2015-004
|View full text |Cite
|
Sign up to set email alerts
|

Meet, prey, like: A study of gifted girls' interactions with social media

Abstract: Gifted and talented girls today struggle with similar social and emotional challenges as those in the past, but their world looks different. With the changes in the media and communication ecology, they are navigating a highly digitised and mediated social landscape. This article explores gifted teenage girls' lived experiences of Facebook, utilising phenomenological research on the experiences of five female students in high profile leadership roles in their secondary schools. The findings suggest these parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Psychologists have considered these reforms to emphasise personal choice and individual responsibility and effort as the route to success (Walkerdine, 2003;Scharff, 2016). These values pervade young people's understanding of themselves as capable and successful within environments where neoliberal values are prioritised (France et al, 2019;Gaerlan-Price, 2020).…”
Section: Neoliberal Selvesmentioning
confidence: 99%
See 4 more Smart Citations
“…Psychologists have considered these reforms to emphasise personal choice and individual responsibility and effort as the route to success (Walkerdine, 2003;Scharff, 2016). These values pervade young people's understanding of themselves as capable and successful within environments where neoliberal values are prioritised (France et al, 2019;Gaerlan-Price, 2020).…”
Section: Neoliberal Selvesmentioning
confidence: 99%
“…High-achieving young women in Aotearoa are thought to face complex and competing expectations from peers, schools and parents (Gaerlan-Price, 2020;. In their research, Gaerlan-Price (2020; found that young female prefects with Aotearoa appear to be constrained by pressures to 'fit in' with the social activities of their peers, facing competing demands from their school to behave, be role models for their peers, and excel in a variety of school domains including their leadership, academic demands, and other extra-curricular activities. Managing these complexities was compounded by these young women's desires to achieve highly and also succeed in meeting standards of successful femininity.…”
Section: High Achievers In Aotearoamentioning
confidence: 99%
See 3 more Smart Citations